The Evolution of HIV Patient Retention and Care in French Guiana: A Broader View From the Système National des Données de Santé - Duplan, Hélène; Rabier, Sébastien; Sudre, Christine; Adriouch, Leila; Lucarelli, Aude; Huber, Florence; Mutricy, Louise; Wojcik, Jean Marc; Vignier, Nicolas; Pascolini, Etienne; Adenis, Antoine; Nacher, Mathieu (Frontiers in Public Health, 2022)
Although the simplification of antiretroviral treatment regimens and follow-up has led to fewer constraints for HIV patients, their follow-up remains of paramount importance to optimize anti-retroviral therapy, to detect and prevent HIV-related morbidity, and prevent secondary infections. The problem of follow-up interruption in French Guiana has been persistent and seemingly impervious to efforts to alleviate it. The objective was to follow the trend of follow-up interuptions and to test the hypothesis that an increasing number of patients was in fact followed by private practitionners. Using the complementary lenses of the hospital HIV cohort and the health insurance information system we looked at the incidence of follow-up interruption and the proportion of patients followed by private practionners. We tallied 803 persons that were not known to have died and who were lost to follow-up. Over time hospital outpatients were lost to follow-up significantly sooner. By contrast, there was a significant trend with more and more patient exclusively followed by private practitionners. While the hospital outpatient care remains by far the most common mode of patient care, there seems to be a gradual erosion of this model in favor of private practice.